The Impact of Digital Transformation on Changes in Work Patterns and Human Resource Welfare in Remote Areas of Indonesia in 2025 - Kuras Purba; Bengettua Simarmata (Jurnal Mamangan, 2025)
Digital transformation has become a key driver of economic and labor market restructuring in Indonesia, including in remote areas that have long faced limited access to infrastructure and economic opportunities. This study aims to examine the impact of digital transformation on changes in work patterns and the welfare of human resources in remote regions of Indonesia in 2025. The research employs a qualitative descriptive approach with socio-economic analysis, utilizing secondary data obtained from government reports, international institutions, and relevant academic literature. The findings indicate that digital transformation has significantly shifted work patterns from traditional sectors toward digital-based employment and digital entrepreneurship, enabling greater flexibility and broader market access for communities in remote areas. Furthermore, digital transformation contributes to improvements in human resource welfare through increased income opportunities, economic efficiency, and enhanced access to education, information, and public services. However, the benefits of digital transformation are not evenly distributed due to disparities in digital infrastructure, limited digital literacy, and employment insecurity associated with platform-based work. Therefore, comprehensive and inclusive policy interventions are required to ensure that digital transformation supports equitable and sustainable economic development in Indonesia’s remote regions